Biodegradation of Used Engine Oil by Pseudomonas sp. Isolated from an Automobile Workshop’s Soil - Muhammad, Abubakar; Adamu, Faggo Abdullahi (Journal of Environmental Microbiology and Toxicology, 2022)
Environmental pollution caused by used engine oil has been on the increase as a result of accidental or deliberate discharge of the oil. Used engine oil is relatively recalcitrant to biodegradation due to the high concentrations of metals from the wear and tear of engine parts. Several physical and chemical methods were employed for the remediation of used engine oil-contaminated soil, but bioremediation remains the most economical especially in remediating polluted soils. Therefore, this work aimed to isolate and screen efficient used engine oil-degrading bacteria from serval automobile workshops located at Gadau town, Itas Gadau, Bauchi state, Nigeria. Soil samples were collected from three different locations and were used to isolate, and screen used engine oil-degrading bacteria. The best degrader was Pseudomonas sp. with 82% degradation of 1% (v/v) of used engine oil after 5 days of aerobic incubation. The result further indicated that degradation occurs best at 1% (v/v) and no degradation was recorded at 3% (v/v) of used engine oil. Pseudomonas sp. can be employed in the field remediation of used engine oil-contaminated soil.